Loucura e cultura: cartografias da extensão de uma clínica poética - Bom-Tempo, Juliana Soares (2008)
This research approaches madness as a complex question which permeates the everyday life and articulates with questions other than those ones of conceptions and practices that put it only in the mental health perspective. Some artistic works which take the risk of inaugurating a new conception of madness allow putting into question some clichés and standards imposed even when an opening to new ways of existenciality is aimed. This work seeks to essay some possibilities of changing the perspective that madness and professional performance follows. It is a critic view of consolidated practices, by proposing a composition of a practice with multiplying interventions. These latter build and are built insofar as they happen in a dialogical relationship with what it makes and how it does. This investigation considers madness not as a deviation but as a possibility of singular existentialities, which become ill only because they are not authorized discursively. That is why it tries to keep an ethic, political, and aesthetic position towards the madman sickening. Based on dances in squares and artistic practices, a new body hints; a new relationship with bodilinesses breaks through old conceptions. In intervening in the everydayness, by putting into motion the transit between madness and culture, a non-place emerges and breaks through established fields. It is a chance of apprehending the invisible, the unexpected, and the passage of one state to another. Based on Foucault, Deleuze, Guattari, Herrmann, and Gil, a contexture of ideas on the clinic is made through new ways of interlacement as if it were fuxicos (patchworks) that once sewed create multiple possibilities of inhabiting movable dimensions of a clinic that privilege making, creating, and poetizing; that goes beyond the standard clinic domains and makes possible to work professionally in the field of culture in favor of a poetical health.